GRAVITATIONAL AND BUCKLING INSTABILITIES OF A RHEOLOGICALLY LAYERED STRUCTURE: IMPLICATIONS FOR SALT DIAPIRISM - Ismail-Zadeh A.T.; Huppert H.E.; Lister J.R. (My University, 2002)
We study the Rayleigh–Taylor instability of a structure consisting of a buoyant layer of viscous fluid overlain by a dense perfectly plastic layer (which is represented by a strongly non-Newtonian fluid with the power-law exponent tending to infinity). The structure is subject to either horizontal extension or shortening and models rocksalt under a brittle overburden. The growth rate and wavelength of the most unstable perturbation to the background pure shear flow are calculated and compared with those of models composed of two viscous layers or of two perfectly plastic layers. The effects of the viscosity and thickness ratios and density contrasts between the two layers are assessed. Considering the viscosity of the buoyant layer to be much less than the effective viscosity of the overlying layer, we obtain the following results. (i) The instability pattern of the plastic–viscous structure is similar to that of a plastic–plastic structure. (ii) The characteristic wavelength, corresponding to the most unstable mode, increases initially with the thickness ratio between the lower and upper layers, but then decreases by a series of abrupt jumps. (iii) The buckling instability induced by rapid horizontal extension or shortening overwhelms the gravitational instability and the growth rate of this instability depends linearly on the effective viscosity ratio. We analyze the energy equation in order to develop an understanding of the mechanisms of instability as the system varies from a viscous fluid through a power-law fluid to a perfectly plastic medium. To test our analytical results we study models of diapirism in the Great Kavir, Iran. We show that a small interdiapir spacing in the salt canopy province and a wide range of spacings in the salt pillow province of the region can be explained by the perfectly plastic sedimentary overburden and horizontal shortening.